Historical consciousness and its role in teaching regional history - Kopeček, Pavel; Krákora, Pavel (Res Gestae. Czasopismo historyczne, 2023)
This text deals with the basic concepts of historical consciousness and regional history and analyses their relationship. Moreover, it deals with the possibilities, challenges, and opportunities offered by regional history concerning the educational process. In conclusion, some research projects focused on this theme are briefly presented. The partial results of the research into the historical consciousness of regional history can also become a platform for a broader discussion focused on the issue of educational standards and the form of the history curriculum in primary and secondary schools.